Global Value Chain Integration and Productivity : Evidence from Enterprise Surveys in Namibia, South Africa, and Swaziland - Winkler, Deborah; Farole, Thomas (World Bank, Washington, DC, 2016)
In order to adequately measure a firm’s participation in GVCs in this context, it is important to first identify the different forms through which GVC integration can affect domestic firms’ productivity. Integrating a country’s domestic suppliers into GVCs increases the possibility for productivity gains through exporting to a buyer abroad or supplying to a multinational in the country. But countries should not neglect the opportunities for productivity gains that GVC participation can provide from a buyer’s perspective. Instead of building a complete array of supply chains at home, firms can join existing supply chains of multinationals through cross-border trade in intermediates and components (Taglioni and Winkler 2015). While Farole and Winkler (2014) focus on the productivity spillovers from multinationals in a country, this note looks at the impact of cross-border sales to international buyers (exporting) or purchases of inputs from international sellers (importing) in GVCs. This note is structured as follows. Section two reviews the relevant literature with regard to productivity effects from GVC participation as well as the role of domestic firm characteristics in this context. Section three introduces the data and econometric model. In section four the author presents our regression results, while section five concludes.